Investigating the need for achievement among junior high school students - da Costa, Augusto; Rachmawati, Indriyana; Laksana, Eko Pramudya (Universitas Negeri Yogyakarta, 2022)
Need for achievement is the encouragement, both within and outside the individual, to perform certain behaviors. This encouragement is needed by individuals to achieve academic achievement in school. The purpose of this study was to determine the percentage of motivation for achieving adolescents in Malang, Indonesia. The research method used is quantitative with a descriptive type of research. The population of this study was 7183 junior high school students. The study led 315 students and sampled using proportional stratified random sampling. The data collection technique uses an achievement motivation scale developed by the researcher himself based on theory and data analysis using frequency in descriptive statistics. The results showed that 69% of adolescents were motivated to perform at a moderate level, 21% at a high level, and 10% at a low level. This means that the level of motivation for achieving students at a moderate level needs to be improved through the support of parents and teachers, so that students can achieve the expected academic success.